SEPARATION OF MECHANICAL VENTILATION - Ida Bagus Wisnu Parbawa Kusuma; I Nengah Kuning Atmajaya (E-Jurnal Medika Udayana, 2014)
The weaning from mechanical ventilation can be defined as the process of letting theventilator either directly or in stages. Indication of weaning from mechanicalventilation, seen from several parameters such as disease processes, PaO2, PEEP,FiO2, pH, Hb, awareness, body temperature, cardiac function, lung function, drugssedative agent or paralysis agent, and psicologic status of patient. Based on thelength of the weaning, can be devided into two, long-term weaning dan short-termweaning. Short-term weaning, such as T-Piece, CPAP, SIMV, and PSV. Long-termweaning, such as T-Piece and Intermitten Mandatory Ventilation. There are two thataffect the length of weaning, such as nonventilator factor and ventilator factor.Nonventilator factor such as sedation drug abuse, malnutision, lack of psychologicalsupport, and lack of support if there is damage to the left ventricle. Ventilator factorsuch as over ventilation and under ventilation. Factor that lead to failure in weaningaffected by respiratory control center, respiratory muscle strength, and load on therespiratory muscles.